Mediasi Dan Arbitrase - Hendra, Muhamad Juzama; Nefri, Johan Edi (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
Dispute resolution plays an important role in maintaining harmony and order in society. This study aims to examine the role of mediation and arbitration in the context of Islamic constitutional law by integrating such approaches with the principles of Islamic law. This study uses a descriptive qualitative approach to answer research questions that focus on an in-depth understanding of mediation and arbitration. Data collection is carried out through literature study and analysis of documents relevant to the research topic. Major data sources include scientific articles, and relevant books. The results of this study address mediation and arbitration, providing a platform for deliberation-based processes where disputing parties can reach agreement through fair dialogue and discussion. Islamic ethics and values in dispute resolution, mediation and arbitration in Islamic law demand a high level of ethics and adherence to Islamic values. This process should be based on Islamic moral and ethical principles, including honesty, justice, and commitment to peace. Islamic principles create a dispute resolution system that is more effective and in accordance with Islamic values. By understanding and respecting Islamic principles, mediation and arbitration can be powerful instruments in creating a fair dispute resolution.